Treatment of Third-Degree Thermal Burns in Dogs with Ozonated Vegetable Oil - Vardanyan, A. V.; Chobanyan, L. V.; Harutyunyan, H. D. (ՀԱԱՀ հիմնադրամ)
When comparing the blood indicators of the animals treated with ozonated vegetable oil with those of the animals treated with 0.2 % furacillin ointment, it becomes vivid that on all research days (3rd, 9th and 17th) the blood indicators of experimental animals recover faster than those of the control animals. Upon the experiments it has been proved that when treating the third-degree burn with ozonated vegetable oil, the burn wound is recovered 3 days earlier than in case of treating it with 0.2 % furacillin ointment. This is due to the reduction of hydration phase and active wound granulation process.
Keywords: Veterinary Science and Animal Breeding